2021
DOI: 10.1073/pnas.2021757118
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling expression and editing preferences of ADAR1 p150 and p110 isoforms

Abstract: Human adenosine deaminase acting on RNA 1 (ADAR1) catalyzes adenosine-to-inosine deamination reactions on double-stranded RNA molecules to regulate cellular responses to endogenous and exogenous RNA. Defective ADAR1 editing leads to disorders such as Aicardi-Goutières syndrome, an autoinflammatory disease that manifests in the brain and skin, and dyschromatosis symmetrica hereditaria, a skin pigmentation disorder. Two ADAR1 protein isoforms, p150 (150 kDa) and p110 (110 kDa), are expressed and can edit RNA, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 43 publications
5
67
0
Order By: Relevance
“…In this study, we performed a transcriptome-wide analysis of thousands of A-to-I sites in human and mouse cells that express Za domain mutant ADAR1 and found that the overall editing efficiency was reduced by loss of ADAR1/Z-RNA interaction. While the reduction in ADAR1 activity in mouse cells applied to whole transcripts, this was particularly evident for 3 0 UTRs in human transcripts, which is in agreement with a recent study (Sun et al, 2021). As introns are spliced out before nuclear export, SINE-derived dsRNA structures in 3 0 UTRs are most likely responsible for the activation of the cytosolic dsRNA sensor MDA5.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we performed a transcriptome-wide analysis of thousands of A-to-I sites in human and mouse cells that express Za domain mutant ADAR1 and found that the overall editing efficiency was reduced by loss of ADAR1/Z-RNA interaction. While the reduction in ADAR1 activity in mouse cells applied to whole transcripts, this was particularly evident for 3 0 UTRs in human transcripts, which is in agreement with a recent study (Sun et al, 2021). As introns are spliced out before nuclear export, SINE-derived dsRNA structures in 3 0 UTRs are most likely responsible for the activation of the cytosolic dsRNA sensor MDA5.…”
Section: Discussionsupporting
confidence: 90%
“…We compared the outcome of our RIP-Seq results that were performed in HEK293 cells with the currently published ADAR1-isoform-specific editome that was also generated in HEK293 cells (Sun et al, 2021). To do so, we employed CrossMap (v0.5.4) (Zhao et al, 2014) to convert the set of identified editing sites to the GRCh38 assembly.…”
Section: Discussionmentioning
confidence: 99%
“…The NES-bearing cytoplasmic ADAR1-p150 isoform is expressed from an interferon-regulated promoter [ 54 ]. Inflammation-mediated interferon signaling thus leads to the cytoplasmic accumulation of this isoform and therefore will boost editing of cytoplasmically localized RNAs [ 55 , 56 ]. In contrast, the nucleo-cytoplasmic shuttling of ADAR1 p110 is controlled by its RNA-bound state [ 45 ].…”
Section: Regulation Of Adar Activitymentioning
confidence: 99%